Directive and Steerable Radiation Pattern using SASPA Array (Journal of Engineering, 2023)
This work examines the ability of a special type of smart antenna array known as Switched Active Switched Parasitic Antenna (SASPA) to produce a directive and electronically steerable radiation pattern. The SASPA array consists of antenna elements that are switchable between active and parasitic states by using P-Intrinsic-N (PIN) diodes. The active element is the element that is supplied by the radio frequency while short-circuiting the terminals of an element in the array results in a parasitic element. Due to the strong mutual coupling between the elements, a directional radiation pattern with high gain and a small beamwidth can be produced with only one active element operating at a time. By changing the parasitic state to the active state sequentially for all elements, the directed radiation pattern can be easily rotated. The antenna array structure used in this work is the uniform circular array (UCA) to achieve symmetrical radiation patterns and full coverage of the entire azimuth plane. Also, a novel method for reducing the mutual coupling effect in SASPA arrays is proposed in this work. By using this method, some parameters of the generated SASPA’s radiation pattern can be controlled. The simulated results obtained from this work depict that an N-element SASPA-UCA produces N-symmetrical, switchable, and steerable radiation patterns with high gain, small beamwidth, and a high Front-to-Back (F/B) ratio. Also, the results show that further improvements in these parameters can be achieved by increasing the number of elements in the array. Additional simulations demonstrate that by including decaying function weight in each element's circuitry, the mutual coupling between the components of the SASPA-UCA array can be minimized. The aforementioned parameters can then be efficiently modified using this mutual coupling reduction.